Language, Culture, and Politeness in Directive Speech Acts of the Lauje Language in Parigi Moutong Regency - Ulinsa Ulinsa; Gazali Gazali; Yunidar Yunidar; Sitti Harisah; Muhammad Rohmadi; Nico Irawan (Universitas Muhammadiyah Malang, 2025)
The Lauje language, spoken by communities in Parigi Moutong Regency, Central Sulawesi, reflects a rich cultural and social identity, yet faces the threat of extinction due to the dominance of Indonesian and the impact of globalization. This study aims to explore the forms, functions, and strategies of directive speech acts in the Lauje language, which remain largely undocumented in linguistic research. A qualitative descriptive approach was employed to achieve this goal. Data was collected through field observation, audio recording of natural conversations, and interviews with native speakers in Moubang Village, a culturally representative Lauje-speaking area. Data collection techniques included eavesdropping, recording, and note-taking, while the analysis involved data reduction, categorization, interpretation, and validation using source and theoretical triangulation. The findings reveal six distinct forms of directive speech acts —commanding, ordering, requesting, asking, suggesting, and advising —each with specific social functions and realized through both direct and indirect strategies. These patterns reflect the speaker's sensitivity to social context, hierarchy, and politeness norms. The study concludes that directive speech acts in Lauje serve not only communicative purposes but also preserve the community's cultural values and relational dynamics. The research contributes to pragmatic studies of regional languages and supports efforts to document and revitalize endangered linguistic heritage in Indonesia.